Effects of polyethylene glycol supplementation on the performances of Cilentana goats grazing woodland and scrubland - Infascelli F.; Cutrignelli M.I.; Bovera F.; Tudisco R.; Zicarelli F.; Calabrò S. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Thirty pregnant goats grazing in woodland and scrubland were randomly allocated to two equal groups (PEG and control). They were individually given 200, 300 and 400 g of concentrate (19.2% CP and 1.0 Milk Feed Unit, equal to 1700 kcal of net energy for lactation, on DM) 45, 30 and 15 days before the delivery, respectively. 10 g/head/day of PEG mixed with a part of concentrate was offered to the PEG group. After parturition (end of January - beginning of February) the concentrate was gradually increased for both groups up to 500 g/head. After weaning of kids (60 days), individual milk yield was recorded every 30 days with analyses for protein, fat, lactose and urea. Quercus ilex and Pirus amygdaliformis were the main woody species present in the grazing areas. No differences were found between groups for kid birth weights and daily weight gain (DWG); the PEG supplement affected only milk yield registered after weaning (1210 vs 1065 g/day; P<0.01), mainly in spring.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)